Capturing the Bigger Picture? Applying Text Analytics for Foster Open Innovation Processes for Sustainability-Oriented Innovation - Wehnert, Peter; Kollwitz, C.; Daiberl, Christofer; Dinter, Barbara; Beckmann, Markus (Sustainability, 2018)

Combining open innovation and knowledge management for a community of practice-an analytics driven approach - Dinter, Barbara; Kollwitz, Christoph; Möslein, Kathrin; Roth, Angela (Proceedings of the Twenty-second Americas Conference on Information Systems, 2016)

Constructing Software-Intensive Methods: A Design Science Research Process with Early Feedback Cycles - Krawatzek, Robert; Hofmann, Marcus; Jacobi, Frieder; Dinter, Barbara (Eighth International Conference on Design Science Research in Information Systems and Technology (DESRIST), 2013)
Methods are a common artifact within design science research (DSR). In the context of a research project we faced the challenge to develop a method and a software artifact in parallel. However, existing work in DSR and method engineering does not explicitly address the simultaneous development of two interdependent artifacts. Therefore, we developed a DSR process that allows the construction of so-called software-intensive methods. It considers the interdependencies of both artifacts and optimizes common DSR processes by including early feedback cycles for intermediate results allowing the identification of initial design weaknesses like missing or dispensable design elements, inappropriate element design and usability flaws. The process has been applied and its feasibility has been demonstrated in the research project. © 2013 Springer-Verlag.
WiSo-Import:2015-04-17:4939
Keywords: design science; early feedback; generate-test cycle; method engineering; research process; software prototype